(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
This research analyses the feasibility of supplying a large size desalination energy demand by marine renewables. The case study is Las Palmas III seawater desalination plant, the largest desalination plant in the Canary Islands (Spain), which is located in the northeast of the island of Gran Canaria. Its average daily water production is 62,614 m³/day, consuming a total of 90,669.52 MWh/year. A constant energy production is needed for the optimal plant operation which raises the possibility of using different renewable technologies in order to reduce the energy fluctuations. In this case, the sea and its wind and wave energy resources are key technologies for supplying desalination plants near the coast. For this reason, different configurations have been simulated combining both technologies and analyzing their pairing in hourly terms to achieve a more stable energy production. The proposed methodology contemplates the identification of the hotspot for the technologies location in terms of environmental constraints and resource assessment (both wind and waves). The subsequent selection of the wind turbine and the wave converter and the energy coverage evaluation. Results tried to establish if the combination of offshore wind and wave energy improves the demand coverage in overall terms and in terms of seasonal match.